2002
DOI: 10.1021/jp026733i
|View full text |Cite
|
Sign up to set email alerts
|

Energies and Dynamics of Photoinduced Electron and Hole Processes on MgO Powders

Abstract: The dynamics of photoinduced formation of electron and hole centers at the surface of MgO powder has been investigated in situ using EPR spectroscopy. Monochromatic excitation of the sample with 282 nm photons leads to creation of well-separated electron and hole centers at the surface. Polychromatic (200-900 nm) irradiation leads to a very different time evolution of the EPR signal of the photoinduced centers. We argue that this difference is due to secondary reactions stimulated by the low energy part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…The photon energy needed for hole generation depends on the coordination state of the anion [21][22][23]: a three-coordinated O 2) ion requires less energy for hole production (for MgO: 4.6 eV) than does a four-coordinated anion in an edge site (5.6 eV) [6,11,24]. We have shown previously that O ) ions formed via UV induced charge separation are exclusively trapped at 3-coordinated sites such as oxygen-terminated corners or kinks.…”
Section: Introductionmentioning
confidence: 99%
“…The photon energy needed for hole generation depends on the coordination state of the anion [21][22][23]: a three-coordinated O 2) ion requires less energy for hole production (for MgO: 4.6 eV) than does a four-coordinated anion in an edge site (5.6 eV) [6,11,24]. We have shown previously that O ) ions formed via UV induced charge separation are exclusively trapped at 3-coordinated sites such as oxygen-terminated corners or kinks.…”
Section: Introductionmentioning
confidence: 99%
“…Knozinger and co-workers [26], reported, using EPR studies, that monochromatic UV irradiation of MgO particles at 5.4 eV (230 nm) and 4.6 eV (270 nm) leads to the ionization of low-coordinated surface oxygen anions (O LC 2 ) -in MgO, forming a localized surface hole state [O -] and a surface-trapped electron. Moreover, they reported [27], that such surface species are as well formed from the polychromatic (200-900 nm) irradiation of MgO with low energy photons (3.9-1.5 eV) resulting in a different dynamics of hole and electron center signals compared to those induced with monochromatic irradiation (282 nm). Thus, based on studies by Knozinger and co-workers [26,27], we propose that in our helium-oxygen-hexane system, UV light (400-700 nm) generated by plasma, as observed in the optical emission spectrum (Fig.…”
Section: Oxidative Conversion Of Hexane In the Presence Of Plasmamentioning
confidence: 99%
“…Moreover, they reported [27], that such surface species are as well formed from the polychromatic (200-900 nm) irradiation of MgO with low energy photons (3.9-1.5 eV) resulting in a different dynamics of hole and electron center signals compared to those induced with monochromatic irradiation (282 nm). Thus, based on studies by Knozinger and co-workers [26,27], we propose that in our helium-oxygen-hexane system, UV light (400-700 nm) generated by plasma, as observed in the optical emission spectrum (Fig. 3), leads to the ionization of the low-coordinated surface oxygen anions (O LC 2 ) -in MgO, forming a localized surface hole state [O -] and a surface-trapped electron (17).…”
Section: Oxidative Conversion Of Hexane In the Presence Of Plasmamentioning
confidence: 99%
“…Alternatively, it was suggested [50][51] that the presence of plasma can also help to create new defect sites on the surface of Li/MgO. Nelson et al [50] and later Knozinger et al [51] reported, using EPR studies, that interaction between UV light and MgO particles can give rise to surface paramagnetic centers (trapped electrons, typically F-centers, [VO]).…”
Section: Oxidative Conversion Of Alkanes At Ambient Conditions Using mentioning
confidence: 99%
“…Nelson et al [50] and later Knozinger et al [51] reported, using EPR studies, that interaction between UV light and MgO particles can give rise to surface paramagnetic centers (trapped electrons, typically F-centers, [VO]). Goodman et al [28] suggested, during methane oxidative coupling, that these [VO]-type defect sites are able to activate C-H bond in the alkane.…”
Section: Oxidative Conversion Of Alkanes At Ambient Conditions Using mentioning
confidence: 99%